Integrating Sensory-Symbolic Aesthetics into Green Roofs Design to Foster Social Engagement and a Culture of Environmental Love - Graciela, Cindy Fiolita; Sanjaya, Ridwan -; Widjaja, Robert Rianto (Soegijapranata Catholic University, 2024)
A culture of environmental love is needed to deal with the ecological crisis. In creating a culture of love for the environment, ecological behavior is needed. Green roofs are one space to create this culture. The case study chosen is PVJ Sky Garden, Bandung which uses symbolic sensory aesthetics to encourage ecological behavior in local communities. The theory used to measure social aspects to encourage ecological behavior is Nguyen Dang's (2022) social impact framework which has 7 points. These points are: 1) social wellbeing, 2) economy, 3) sustainable development, 4) mood state, 5) collective identity, 6) place identity, and 7) physical benefits. The research method used is qualitative research using in-depth interviews, observations and questionnaires to mall visitors. The result of this research is a symbolic-sensory aesthetic model that influences social aspects to encourage ecological behavior to become a culture of environmental love. The social impact framework points of sustainable development are the most dominant, followed by economic points and place identity. These 3 points have an important role in encouraging ecological behavior to create a culture of environmental love in the local community at PVJ Sky Garden